Peran Analisis Podcast Terhadap Media Pembelajaran Digital Mahasiswa di Era Milenial - Sariski, Aldo; Tanjung, Salsas Bila Juniyanti; Nirwana, Rena Putri; Julio, Christopher Elia; Nandita, Lufna; Rasyad, Pasha Athallah; Hibatullah, Abdurrafi; Handhani, Muhammad Gading Bintang; Tambunan, Daniel; Herley, Airiique Bintang Merah; Zulfikar, Faiz Raudhin; S, Subakdi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of digital technology in the millennial era has revolutionized the way students obtain and process information, especially in the context of higher education. Podcasts, as an audio-based digital learning medium, offer flexibility, accessibility and special appeal for the younger generation who are familiar with digital content. This article analyzes the role of podcasts as a legal learning medium with a case study of three episodes of the